GREEK LOAN-WORDS IN THE VULGATE NEW TESTAMENT AND THE LATIN APOSTOLIC FATHERS. (2019) - BERGREN, THEODORE A.
Abstract : Early Latin Christian documents translated from Greek (e.g., Latin translations of the Greek New Testament) contain a large number of Greek loan-words. This article attempts to collect and catalogue the Greek loan-words found in the Vulgate New Testament and the early Latin versions of the Apostolic Fathers. In this literature I have identified some 420 loan-words. The purpose of this article is to systematically categorize, analyze, and comment on these loan-words. In the main section of the article the loan-words are divided into discrete content groups based on their origin and/or meaning. These groups include: (1.) words that originated in Hebrew or Aramaic Vorlagen and that were then transliterated into Greek and then Latin; (2.) words with biblical or ecclesiological orientation that are found exclusively or predominantly in early Christian Latin writings; (3.) words that fall into distinct categories of items, persons or places (e.g., "animals, " "items of clothing, " "gems and minerals, " "human occupations"); and (4.) words of a general character that do not fit in any of the above categories. In this section of the article are listed, for each loan-word: first, the Latin word; second, the Greek Vorlage; third, the meaning(s) of the Latin word; and fourth, one example of a passage in the Vulgate New Testament or the Latin Apostolic Fathers in which the Latin word may be found. Loan-words with special characteristics (e.g., Latin hapax legomena) are commented on individually.